Photodynamic Therapy: Light Harvesting and Photoemission by Nanoparticles for Photodynamic Therapy (Part. Part. Syst. Charact. 1/2014). (January 2014) - Arguinzoniz, Amaia Garaikoetxea; Ruggiero, Emmanuel; Habtemariam, Abraha; Hernández‐Gil, Javier; Salassa, Luca; Mareque‐Rivas, Juan C.
<x xml:space="preserve">Abstract</x> Juan C. Mareque‐Rivas and co‐workers report on page 46 the most recent advances in utilizing light harvesting and photoemission by quantum dots and up‐converting nanoparticles for photodynamic therapy (PDT) applications. The image, which imitates the official flag of the Basque Country (ikurriña), illustrates a nanoparticle harvesting visible and near infrared light surrounded by different classes of photoactivatable prodrugs targeting selective killing of cancer cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>